Evaluating the Therapeutic Effect of Low‐Intensity Transcranial Ultrasound on Traumatic Brain Injury With Diffusion Kurtosis Imaging. Issue 2 (30th January 2020) - Zheng, Tao; Yuan, Yi; Yang, Haoxiang; Du, Juan; Wu, Shuo; Jin, Yinglan; Wang, Zhanqiu; Liu, Defeng; Shi, Qinglei; Wang, Xiaohan; Liu, Lanxiang
Abstract : Background: Low‐intensity transcranial ultrasound (LITUS) has a therapeutic effect on traumatic brain injury (TBI). Diffusion kurtosis imaging (DKI) might be able to evaluate the effect changes of injured brain microstructure. Purpose: To evaluate the therapeutic effect of LITUS in a moderate TBI rat model with DKI parameters. Study Type: Prospective case–control animal study. Animal Model: Forty‐five rats were randomly divided into sham control, TBI, and LITUS treatment groups ( n = 15). Field Strength/Sequence: Single‐shot spin echo echo‐planar imaging and fast T2 WI sequences at 3.0T. Assessment: DKI parameters were obtained on days 1, 7, 14, 21, 28, 35, and 42 after TBI. Statistical Tests: For the mean kurtosis (MK), axial kurtosis (Ka), and radial kurtosis (Kr) values, groups were compared using a two‐way analysis of variance (ANOVA). Results: LITUS inhibited TBI and caused MK values to increase significantly during the early stage (LITUS vs. TBI, day 7, adjusted P < 0.0001) and decrease during the late stage (LITUS vs. TBI, day 42, adjusted P = 0.0156) in the damaged cortex. In the thalamus, the MK value of the TBI group began to rise on day 7, with no change observed in the LITUS group. TBI increases Ka value during the early stage in the cortex and decreases during the late stage in the cortex and thalamus. LITUS inhibited these Ka changes (LITUS vs. TBI, day 7, adjusted P = 0.0014; LITUS vs. TBI, day 42, adjusted P = 0.0026 and 0.0478, respectively, for cortex and thalamus). The Kr value increased slightly during the early stage in the cortex (TBI vs. Sham, day 1, adjusted P = 0.0016). Data Conclusion: The DKI parameter, particularly the MK value, evaluates primary cortical injury as well as the secondary brain injury that could not be detected by conventional T2 WI. Level of Evidence: 1 Technical Efficacy Stage: 4 J. Magn. Reson. Imaging 2020;52:520–531.